Educação médica na escola: experiência de estudantes de Medicina em novo cenário de prática - Beaugrand, Annick (2023)
In the teaching and learning process, experience in professional practice has a strategic importance in the training of medical students. The practical activities within the curricular structure consent the student to have a better understanding of the population's real health needs and stimulates a broad and critical thinking. This work proposes to contribute to the integral formation of medical students through actions of promotion, prevention, and health care of student practice on pediatrics discipline. A qualitative research-action at Federal University of Rio Grande do Norte - UFRN was conducted by undergraduate medical students, integrating the school, with students from a kindergarten, elementary middle, and high school, and evaluating their practice. This work comprised the phases: identification of the problem; recruitment of participants, field preparation workshop; intervention; and evaluation of this intervention. Data were collected through semi-structured interviews and data were analyzed using Bardin's categorical thematic content analysis methods. Among the reports of the interviews with medical students, 5 categories emerge: situational diagnosis of the school environment, school as a space for practical activity, student feelings in the face of the new practice scenario, difficulties with pediatric care and the impact of the experience on the formation of the medical student. Among the interview reports with the medical students, the importance of a health program at school stands out, inserted, and integrated into the daily life and school culture, to broaden the experiences within a scenario of the everyday life of children and adolescents, for the undergraduate curriculum in medicine area.